Development of capric acid-stearic acid-palmitic acid low-eutectic phase change material with expanded graphite for thermal energy storage. (21st February 2022) - Du, Wenqing; Fei, Hua; Pan, Yucheng; He, Qian; Zhou, Jiahong; Liang, Ximei
Highlights: CA-SA-PA prepared by melt blending and vacuum adsorption has lowest eutectic point. Phase transition temperature and latent heat of CA-SA-PA/EG are 25.39℃ and 140.22 J/g. CA-SA-PA is evenly adsorbed into the porous structure of EG without chemical reaction. CA-SA-PA/EG has good thermal energy storage ability and chemical stability. Abstract: Excessive building energy consumption and shortage of fuel resources promote the vigorous development of phase change energy storage technology. The application of phase change materials (PCMs) in the construction industry can reduce indoor temperature fluctuation and the load of energy consuming equipment. To explore PCMs for thermal energy storage in the field of building energy conservation, ternary low eutectic is prepared by capric acid (CA), stearic acid (SA) and palmitic acid (PA). Take into consideration of the poor thermal conductivity and easy leakage in molten state of organic PCMs, with porous matrix of expanded graphite (EG) as the carrier, CA-SA-PA/EG with a mass ratio of CA-SA-PA to EG of 12:1 was prepared by vacuum adsorption method. It is measured by differential scanning calorimetry (DSC) that CA-SA-PA/EG has a melting temperature of 25.39 ℃ and a melting latent heat of 140.22 J/g, which are higher than that of CA-SA-PA, indicating the addition of EG slightly enhances the phase transition characteristics of CA-SA-PA. The identification of microstructure, chemical structure and crystal structure confirmed that CA-SA-PA was evenly adsorbed into the pores of EG, and they have good compatibility without chemical reaction. Besides, the thermal performance and reliability analysis also show that CA-SA-PA/EG has high thermal conductivity of 3.059 W / m ∙ K, good heat storage and release performance and stable thermal and chemical properties, and is a potential candidate in the application field of latent heat storage.